How to personalize learning : a practical guide for getting started and going deeper - Bray, Barbara, 1948-; McClaskey, Kathleen, ....- (Thousand Oaks (Calif.) : Corwin - Sage, 2017)
In this field guide, the authors take classroom teachers more deeply into the journey to personalize learning, giving them the tools, skills, and resources they need to level the playing field and start personalizing learning for all of their students. Practical from the start, it begins with an activity that will help teachers, school staff, and other stakeholders deeply understand the difference between personalization, individualization, and differentiation and begin building a common vision, culture, and language that supports personalized learning using the Universal Design for Learning (R) (UDL) framework. The book moves readers through a process of steps and activities to begin personalizing learning, each stage leveraging the UDL principles of Access, Engagement, and Expression to create a powerful shift in classroom dynamics by guiding learners to become self-directed, self-monitoring, and self-motivated.
Foreword by Luis Perez